Pelestarian Terbitan Berkala Koleksi Perpustakaan Nasional Republik Indonesia dengan Metode Penjilidan “Malaysia” - Damaji Ratmono (Media Pustakawan, 2021)
Preservation of library materials or library collections is an effort made so that library materials can be used by future generations. This paper describes the "Malaysian" binding method used by the Sub Division of Technical Binding Materials of the National Library of Indonesia in preserving the collection of periodicals such as tabloids and newspapers. Apart from that, this paper also describes some of the advantages and disadvantages seen in the use of the "Malaysian" method as well as the early history of using this method in preserving the collection of periodicals in the National Library of Indonesia. This writing aims to make readers, especially library managers, know and gain insight into the "Malaysian" binding method. This writing method is through descriptive research with a qualitative approach. Methods of data collection are carried out through the field research, interviews, and literature study. The results show that the National Library of Indonesia uses this method after studying it from Malaysia in May 1990. From observations it is also known that this method has several advantages, namely the binding result is stronger, the collection is more preserved, the binding can be assembled and has an aesthetic side. Meanwhile, the disadvantages of this binding method are that the process tends to be longer, more expensive, cannot be put on too many shelves because the collection will shift backwards, the pages tend to come off easily if the stitches are not strong enough, and can only be used in binding periodical collections.